Electrical conductivity and thermal properties of functionalized carbon nanotubes/polyurethane composites - Lima,Aline M. F. (2012)
Multi-walled carbon nanotubes (MWCNTs) functionalized with amine and carboxyl groups were used to prepare polyurethane/MWCNT nanocomposites in two distinct concentrations: a lower value of 1 mass% (spray coating) and a higher one of ~50 mass% (buckypaper based). The MWCNT-NH2 sample contained only 0.5 mass% of amine groups, whereas MWCNT-COOH contained 5 mass% of carboxyl groups. The MWCNT functionalized with low amine group content showed improved thermal properties when compared to neat thermoplastic polyurethane (TPU) and MWCNT-COOH based nanocomposites. The electrical conductivity of the polyurethane elastomer was greatly increased from 10-12 to ~10-5 S cm-1in the 1 mass% nanotube composite and to 7 S cm-1for the MWCNT-NH2 buckypaper-based nanocomposite. Furthermore, the relative high content of functional groups in the MWCNT-COOH sample, which disrupt the sp²structure in the nanotube walls, led to inferior properties; for instance the conductivity of the buckypaper based composite is one order of magnitude lower when using MWCNT-COOH in comparison with the MWCNT-NH2. These results show the range of property design possibilities available with the elastomeric polyurethane nanocomposite by tailoring the functional group content and the carbon nanotube load.